2018
DOI: 10.12659/msm.910811
|View full text |Cite
|
Sign up to set email alerts
|

Marital Status and Survival of Patients with Hormone Receptor-Positive Male Breast Cancer: A Surveillance, Epidemiology, and End Results (SEER) Population-Based Study

Abstract: BackgroundAlthough marital status has been reported as a prognostic factor in different cancer types, its prognostic effect on hormone receptor (HR) positive male breast cancer (MBC) is unclear. The objective of the present analysis was to assess the effects of marital status on survival in patients with HR positive MBC.Material/MethodsPatients diagnosed with HR positive MBC from 1990 to 2014 in the Surveillance, Epidemiology, and End Results (SEER) database were included. Kaplan-Meier survival analysis and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
(45 reference statements)
0
12
0
1
Order By: Relevance
“…The OS and CSS of unmarried patients were much higher, especially compared to those of widowed patients. There are many similar reports in the recent literature regarding several other types of cancers, such as chondrosarcoma [26], oral cavity squamous cell carcinoma [27], gastric cancer [28], breast cancer [29], testicular cancer [30], and nasopharyngeal carcinoma [31].…”
Section: Discussionmentioning
confidence: 99%
“…The OS and CSS of unmarried patients were much higher, especially compared to those of widowed patients. There are many similar reports in the recent literature regarding several other types of cancers, such as chondrosarcoma [26], oral cavity squamous cell carcinoma [27], gastric cancer [28], breast cancer [29], testicular cancer [30], and nasopharyngeal carcinoma [31].…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic factors, including household income, education level, and marital status, have previously been confirmed to affect tumor prognosis [1316]. CRC is the third most common cancer and the third leading cause of cancer death in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we found that patients over 70 years harbor a lower OS than the younger patients. Moreover, the mortality risk of unmarried MBC patients is significantly increased compared to married populations, despite the undefined mechanism by which this occurs (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%